2000
DOI: 10.2307/2657188
|View full text |Cite
|
Sign up to set email alerts
|

What Governs Protein Content of Pollen: Pollinator Preferences, Pollen-Pistil Interactions, or Phylogeny?

Abstract: Pollen ranges from 2.5% to 61% protein content. Most pollen proteins are likely to be enzymes that function during pollen tube growth and subsequent fertilization, but the vast range of protein quantity may not reflect only pollen-pistil interactions. Because numerous vertebrate and invertebrate floral visitors consume pollen for protein, protein content may influence floral host choice. Additionally, many floral visitors pollinate their host plants. If protein content influences pollinator visitation, then po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
357
1
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 235 publications
(381 citation statements)
references
References 45 publications
11
357
1
12
Order By: Relevance
“…To test if foraging preferences among host-plant species were associated with pollen nutritional quality, we collected extensive simultaneous foraging visitation data for B. impatiens colonies to multiple plant species (controlling for phenology and floral area/resource availability) and analyzed the nutritional content (carbohydrate, protein, and lipid concentrations) of each host-plant species' pollen ( Table 1). All nutritional values were within the expected range for pollen (18). Foraging data and methodology were previously published in ref.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To test if foraging preferences among host-plant species were associated with pollen nutritional quality, we collected extensive simultaneous foraging visitation data for B. impatiens colonies to multiple plant species (controlling for phenology and floral area/resource availability) and analyzed the nutritional content (carbohydrate, protein, and lipid concentrations) of each host-plant species' pollen ( Table 1). All nutritional values were within the expected range for pollen (18). Foraging data and methodology were previously published in ref.…”
Section: Resultsmentioning
confidence: 99%
“…However, pollen nutritional quality varies widely among plant species, ranging from 2-60% protein and 1-20% lipids by weight (10,18); thus, it likely is critical that bees selectively collect pollen species with the necessary nutritional quality to support their needs (1). The protein and amino acid concentrations of pollen modulate immunocompetence in honey bees (16,19) and reproduction (ovary activation and larval development) in bumble bees (12,14,(20)(21)(22).…”
mentioning
confidence: 99%
“…Pollen may also be affected by Effects of pollen protein content on Effects of pollen protein content on B. terrestris B. terrestris factors such as drying, ageing, or storage conditions (Ribeiro et al, 1996). The protein content of pollen can also vary widely, ranging from 2.5 to 61% and is generally accepted as a reliable measure of its nutritional value (Roulston et al, 2000). Similarly, the crude protein content of pollen collected by the honey bee typically ranges from 7.5 to 35% (Schmidt and Buchmann, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Although it is not possible to affirm, the lower ingestion of Apiaceae pollens might be due to the higher protein content. Roulston et al (2000) recorded that the protein content of the Z. mays pollen is 23.9%, and 29.0% for the Anthriscus sylvestris (L.) (Apiacae). Nevertheless, data in the literature as to the protein content of Apiaceae pollens evaluated in the present study were not found.…”
Section: Ingestion Of Pollens By C Maculatamentioning
confidence: 99%
“…The ingestion of corn pollen grains (Zea mays L., Poaceae) by larvae and adult C. maculata has been recorded, and whose mean average protein content was estimated at 24% (Roulston et al, 2000), making up quite an attractive botanical species for this coccinellid (Smith, 1965;Lundgren et al, 2005;Weber and Lundgren, 2011). Hippodamia convergens Guérin-Méneville, 1842 (Coleoptera: Coccinelidae) adults collected in organic vegetable crops were also determined as being able to ingest pollen grains from ten botanical families, including Apiaceae, although their species were not identified (Medeiros et al, 2010).…”
Section: Introductionmentioning
confidence: 99%